2019
DOI: 10.1002/cplu.201900512
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of a Coral‐Like Cobalt Iron Oxyhydroxide Porous Nanoarray: An Efficient Catalyst for Oxygen Evolution Reactions

Abstract: The design of high‐efficiency and cost‐effective electrocatalysts is one of the most crucial factors for facilitating the oxygen evolution reaction (OER). Therefore, we prepared CoxFe1‐xOOH with coral‐like nanonet arrays on carbon cloth (CC) as high‐performance OER catalysts by a facile hydrothermal method. The resulting CoxFe1‐xOOH was characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and X‐ray photoelectron spectrometry. When serving as a catalyst electrode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…[12] Manjunatha [13] et al demonstrated that hydrothermally generated NiS 2 materials with different morphologies and structures exhibit different OER performances. Furthermore, the combination of NiS 2 with a suitable carbonaceous material can generate a composite with improved conductivity and electron transfer, [14] thus improving upon the redox activity [15] and electrocatalytic properties of the parent catalyst. [7,16] There are many approaches for preparing metal sulfides with abundant redox active site, such as electrodeposition, [17] hydrothermal and reflux technology.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Manjunatha [13] et al demonstrated that hydrothermally generated NiS 2 materials with different morphologies and structures exhibit different OER performances. Furthermore, the combination of NiS 2 with a suitable carbonaceous material can generate a composite with improved conductivity and electron transfer, [14] thus improving upon the redox activity [15] and electrocatalytic properties of the parent catalyst. [7,16] There are many approaches for preparing metal sulfides with abundant redox active site, such as electrodeposition, [17] hydrothermal and reflux technology.…”
Section: Introductionmentioning
confidence: 99%